Yemen is Free of COVID-19 as of April, 2020: A Survey - Hussein O. Kadi (Current Overview on Disease and Health Research Vol. 1, 2022)
Among all the countries, Yemen is free of corona virus, and no single case has been recorded till today. The factors that made Yemen free of corona virus infection: Yemenis mobility, habits, food, khat chewing, consume tobacco and governmental actions. The factors that made Yemen free of corona virus infection can be considered as a guide for precautionary measures and to limit the spread of the epidemic, prevent it and made Yemen free of COVID-19 infection and resistance to virus if any.